Selecting the Honeywords from Existing User’s Passwords Using Improved Hashing and Salting Algorithm - Moe, Khin Su Myat; Win, Thanda (International Journal of Computer (IJC), 2018)
Nowadays, hashing passwords become the most essential tool for various web applications for making login process. However, password hashing takes many times for processing and it has become easier for attackers to crack hashing passwords from legitimate users by using brute force attack. Brute force attack is one of the dangerous attacks for password hashing techniques. Therefore, the legitimate user accounts are stored the passwords with honeywords using honeywords generation algorithm in order to prevent from brute force attack. Honeywords generation method is to produce the fake or decoy password for deceiving the attackers. However, the existing honeywords generation algorithm meets the storage overhead problem. So, we are implementing the improved honeywords generation method which decreases the storage overhead problem and also it addresses the majority of the drawbacks of existing honeywords generation methods. Moreover, we store the password and honeywords into the database using a unique hashing algorithm with very low time complexity as most of the steps involved simple binary operations.